PENGARUH DESAIN GAMBAR, MEREK DAN KUALITAS PRODUK KAOS TERHADAP KEPUTUSAN PEMBELIAN DI DISTRO IDIOMATIC YOGYAKARTA - Wisnu Kusuma Sumarno Dwi Saputra (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
This study aims to analyze the influence of graphic design, brand, and product on purchase decisions and determine the dominant factor influencing purchase decisions on products t-shirt in Distro Idiomatic Yogyakarta. This research was conducted in Distro Idiomatic Yogyakarta using samples of 100 consumers in Distro Idiomatic Yogyakarta taken by convenience sampling technique. Hypothesis testing, using multiple linear regression analysis, while data processing using SPSS version 20. The results showed that (1) graphic design have a significant effect on purchase decisions (2) brand have a significant effect on purchase decisions (3) product quality have a significant effect on purchase decisions (4) the dominant factor influencing purchase decision is graphic design. The conclusion of this study, that all hypothesis are accepted. Keywords: graphic design, brand, product quality, purchase decision